Elevated Serum Sialic Acid Levels May be Associated With Diabetes Retinopathy: A Cross-Sectional Study in Ghana - Owiredu, William K. B. A; Obirikorang, Christian; Agoe, Alberta Boye; Acheampong, Emmanuel; Anto, Enoch Odame; Amanquah, Seth D.; Agbodzakey, Hope; Adu, Evans Asamoah; Owusu, Hubert (Frontiers in Clinical Diabetes and Healthcare, 2022)
This study determined the association between serum sialic acid (SSA) and metabolic risk factors in Ghanaian Type 2 diabetes (T2DM) with and without micro vascular complications. This cross-sectional study recruited 150 T2DM out-patients visiting the diabetic Clinic at the Tema General Hospital, Ghana. Fasting blood samples were collected and analyzed for Total Cholesterol (TC), Triglyceride (TG), Low Density Lipoprotein Cholesterol (LDL-C), High Density Lipoprotein Cholesterol (HDL-C), Fasting Plasma Glucose (FPG), Glycated Haemoglobin (HbA1c), SSA and C-Reactive Protein. SSA levels were significantly higher in diabetics with retinopathy (210.12 ± 85.09mg/dl) compared with those with nephropathy and those without complication (p-value= 0.005). Body adiposity index (BAI) (r= -0.419, p-value = 0.037) and Triglyceride (r= -0.576, p-value = 0.003), had a moderate negative correlation with SSA levels. In a One-Way Analysis of Covariance (Adjusted for TG and BAI), SSA could distinguish between diabetics with retinopathy and those without complications (p-value = 0.004) but not nephropathy (p-value = 0.099). Within group linear regression analysis showed that Elevated serum sialic acid was found in type 2 diabetic patients with retinopathic micro-vascular complications. Therefore, estimation of sialic acid levels may help with the early prediction and prevention of microvascular complications occurring due to diabetes, thereby decreasing the mortality and morbidity.